Plasmapheresis for Spur Cell Anemia in a Patient with Alcoholic Liver Cirrhosis - Kenji Miki; Takashi Maruki; Shinsaku Imashuku (Case Reports in Hematology)
Background. Spur cell anemia (SCA) is a cause of hemolytic anemia in patients with alcoholic liver cirrhosis. Because dyslipidemia is related to the development of spur cells, SCA was previously treated with plasmapheresis. Case Report. A 52-year-old Japanese man with SCA associated with alcoholic liver cirrhosis (Child–Pugh C) underwent two rounds of plasmapheresis. Clinical features and serum lipid concentrations were compared before and after plasmapheresis. Although indirect hyperbilirubinemia and SCA persisted after plasmapheresis, reticulocyte counts significantly decreased from 22.4% to 4.5%, and Hb levels improved without red cell transfusions. Analysis of lipids showed that total and free cholesterol, HDL cholesterol, phospholipid, and apo-AI concentrations, all of which were reduced before plasmapheresis, had improved after treatment, while LDL cholesterol, lipoprotein (a), and apo-AII concentrations, which were also reduced before plasmapheresis, remained unchanged. Conclusions. Despite plasmapheresis partially ameliorating the degree of hemolysis, the persistence of SCA may have been linked with the lack of improvement in certain types of lipid metabolism.